A variational approach for an electro‐elastic unilateral contact problem - Matei, Andaluzi (Mathematical Modelling and Analysis, 2009)
We consider a mechanical model which describes the frictionless unilateral contact between an electro‐elastic body and a rigid electrically non‐conductive foundation. For this model, a mixed variational formulation is provided. Then, using elements of the saddle point theory and a fixed point technique, an abstract result is proved. Based on this result, the existence of a unique weak solution of the mechanical problem is established.First published online: 14 Oct 2010